(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Red chilies are a horticultural commodity that is susceptible to damage, resulting in a decrease in product quality. The decline in the quality of chilies after harvest occurs due to the ongoing respiration process, so that the chilies wilt (dry) or rot. Other damage to chilies can also occur due to rotting caused by microbes. Therefore, the red chilies produced by the Samarasa farmer group have been directly sold or used by themselves. If the harvest is large in quantity, it will be sold at a cheaper price. This is done because it is feared that red chili harvest products that are stored for a long time will rot and become unsellable. This service activity aims to provide training and assistance regarding post-harvest handling of red chilies so that they can improve their quality and make their shelf life longer. Several stages of service activities carried out include coordination with partners, post-harvest handling training, discussion and evaluation. This activity went well and smoothly. Evaluation results from questionnaires filled out by participants showed an increase in farmers’ knowledge and skills regarding how to handle post-harvest red chilies with an increase of 24% and 12% respectively after attending the training.